2017
DOI: 10.1007/s40519-016-0347-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in depressed and non-depressed patients with obesity

Abstract: PurposeObesity and depression have both been shown to be associated with reduced physical activity (PA). However, most studies have not applied objective measures to determine PA in patients. Moreover, to our knowledge, no studies are available comparing depressed and non-depressed patients with regard to PA.MethodsWe investigated PA in 47 patients with both obesity and depression, 70 non-depressed patients with obesity, and 71 non-depressed and non-obese healthy control participants using the SenseWear™ Armba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
(62 reference statements)
3
17
0
1
Order By: Relevance
“…A high BMI and depression are two current problems in society carrying a significant burden in terms of disease, functional disability and mortality [3,19,20,22,39,40]. In line with our findings, it has been found that obesity increases the risk of depression [41,42] and that the reverse is also true [43], with there being a bidirectional relationship.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A high BMI and depression are two current problems in society carrying a significant burden in terms of disease, functional disability and mortality [3,19,20,22,39,40]. In line with our findings, it has been found that obesity increases the risk of depression [41,42] and that the reverse is also true [43], with there being a bidirectional relationship.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our findings, it has been found that obesity increases the risk of depression [41,42] and that the reverse is also true [43], with there being a bidirectional relationship. Physical activity seems to have a significant relationship with depression [39,44,45] and with overweight and obesity [5,46]. A possible solution to improve both pathologies is PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No systematic intervention took place between the two assessments, apart from many of the obese participants receiving information on healthy nutrition and physical activity while waiting for an appointment for a stomach reduction. Data from the baseline assessment has been published elsewhere ( 1 , 2 , 11 , 25 , 26 ), while results from the follow-up assessment have not yet been presented.…”
Section: Methodsmentioning
confidence: 99%
“…It is often noted that a lack of PA is linked to depressive symptoms. Similarly, obese individuals show decreased PA, possibly due to limited function of their musculoskeletal system or sleep disturbances; this includes obstructive sleep apnoea syndrome (OSAS), which is accompanied by increased daytime sleepiness and elevated, pro-somnogenic cytokine levels [166,171,172]. However, a lack of physical activity may also be a causal factor contributing to the development of obesity.…”
Section: Depressionmentioning
confidence: 99%